2009
DOI: 10.1128/aem.02492-08
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-Species Genomic Microarray Analysis of Fecal Samples Reveals Differential Transcriptional Responses of Bifidobacteria in Breast- and Formula-Fed Infants

Abstract: Although their exact function remains enigmatic, bifidobacteria are among the first colonizers of the newborn infant gut and further develop into abundant communities, notably in response to diet. Therefore, the transcriptional responses of bifidobacteria in rapidly processed fecal samples from young infants that were fed either breast milk or a formula containing a mixture of galacto-and fructo-oligosaccharides were studied. The presence and diversity of the bifidobacterial fecal communities were determined u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
66
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 67 publications
8
66
0
2
Order By: Relevance
“…Although genes related to formate and acetate production were found to be overrepresented in the metatranscriptome compared with the metagenome, transcripts of other Short Chain Fatty Acids (SCFAs) and lactate fermentation pathways were also frequently detected. Notably, carbohydrate utilization and central metabolism functions were also overrepresented in fecal communities, but appeared to be more dedicated to the degradation of complex carbohydrates rather than simple sugars (Klaassens et al, 2009;Turnbaugh et al, 2010). Moreover, shotgun metaproteomics revealed the enrichment of translation, energy production and carbohydrate metabolism in feces (Verberkmoes et al, 2009).…”
Section: Microbiome Of Small Intestine Is Less Complex Than That Of Tmentioning
confidence: 99%
“…Although genes related to formate and acetate production were found to be overrepresented in the metatranscriptome compared with the metagenome, transcripts of other Short Chain Fatty Acids (SCFAs) and lactate fermentation pathways were also frequently detected. Notably, carbohydrate utilization and central metabolism functions were also overrepresented in fecal communities, but appeared to be more dedicated to the degradation of complex carbohydrates rather than simple sugars (Klaassens et al, 2009;Turnbaugh et al, 2010). Moreover, shotgun metaproteomics revealed the enrichment of translation, energy production and carbohydrate metabolism in feces (Verberkmoes et al, 2009).…”
Section: Microbiome Of Small Intestine Is Less Complex Than That Of Tmentioning
confidence: 99%
“…Several studies found bifidobacteria to be significantly greater in BF infants 18,23,26,28,33,36,37,39,47,51 ; Fan and colleagues 26 reported roughly double the relative abundance of bifidobacteria in BF than FF infants. Bifidobacteria have been shown to account for 70% of the sequences of exclusively breastfed (EBF) infants 40 and appear earlier in the feces of EBF than in FF infants 38 In addition, infants who were exclusively breastfed in early life maintained greater colonization with bifidobacteria later in infancy.…”
Section: (Finland)mentioning
confidence: 99%
“…From the first wk of life, different colonization patterns are present in BF and FF infants. 26,49 The fecal microbiota of BF infants is more stable over time, 26,39 and characterized by a lower alpha-diversity compared to FF infants. 15,23,31,33 Exclusive breastfeeding is inversely related to alphadiversity in 3 mo-old infants.…”
Section: (Finland)mentioning
confidence: 99%
See 2 more Smart Citations